FINANCIAL AND INVESTMENT TOOLS FOR PROMOTING THE CIRCULAR ECONOMY: SUSTAINABLE DEVELOPMENT AND CLIMATE NEUTRALITY AS TRIGGERS FOR THE GREENING OF INTERNATIONAL CAPITAL MARKETS - GROD, Myhailo; REZNIKOVA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the article is to identify sustainable development and climate neutrality as triggers for the greening of international capital markets, which will begin the process of identifying a class of financial and investment instruments that contribute to the development of a circular economy. It is argued that the inclusion of social and environmental factors in determining the quality of financial and investment assets will become a new reality, indicating that the financial sector will play a key role in mobilizing the capital needed to implement the global agenda for sustainable development and the development of a circular economy. Sustainable finance will be an end in itself and a precondition for facilitating and accelerating a circular, green and sustainable transition. It has been established that the concept of the circular economy (CE) is still in the stage of theoretical construction, and its final definition is still far from reaching a consensus position in the scientific community. An analysis of the fundamental positions and beliefs of representatives of the conservative, systemic, evolutionary, synergetic, integrated, process, resource, commercial, anthropocentric, environmental and integral approaches made it possible to establish the heterogeneity of ideas regarding the transformational potential of the circular economy for the implementation of green, energy transitions and achievements. climate neutrality and sustainable development. Discussion about the so-called. forced "greening" of international capital markets, international finance and investment, state aid (subsidies and purchases), including to encourage the development of a circular economy, is recognized as contraversion. It is proposed to start a discussion on the development of an algorithm for including future economic benefits from adapted circular business models in business valuation and adequately reflecting them in accounting reports in order to protect investors from unweighted investment strategies, therefore, the issue of attributing investments in a cyclical production process to the class of intangible assets becomes especially acute. (given that the benefits to companies and society will only be felt in the long term). From the standpoint of CE funding, it is promising to study the categories of "sustainable investment" and "eco-friendly investment". There has been a marked lack of research linking CE to sustainable investment in general. While CE appears to be one of the main beneficiaries of the sustainable investment megatrend, at the company level, there is no evidence of an increase in the volume of their financing by “sustainable investors”, nor is it established that the circular activity of companies has helped to accelerate the process of obtaining funding, and also that companies are actively starting to create CE Development Assistance Funds. It has been proven that the integration of CE principles into financial instruments for the development of sustainability (sustainable development, low-carbon economy, climate neutrality) leads to the expansion of the functionality of green bonds and transitional bonds as part of the category of ESG bonds issued to finance the energy and circular transition of companies. While most existing green bonds do not integrate cyclical principles, the requirement that green bonds have a well-defined “use of earnings” is important for CE funding precisely because green bonds are able to integrate cyclical principles into a linear production system. In the context of green bonds, it is initiatives to promote circular principles of waste management and resource use that constitute the fourth largest category of "use of green bond proceeds in the world". It is argued that investments in the circular economy can contribute to the achievement of several sustainable development goals, and therefore green finance and sustainable finance can be considered as components of circular finance. The potential of using CBDCs for the development of a closed-loop economy is considered. Of particular interest is the development of a line of green digital finance, including one based on CBDS. Further research into the impact of environmental, social and governance (ESG) factors on shaping the international business environment will play an important role in greening the practice of asset management. The volume of investments in the development of the circular economy in state packages of green incentives was estimated. It is established that the green economy stimulates transformational shifts in the field of international finance, initiating the development of a new class of financial assets: (1) green finance; (2) sustainable finances; (3) finance for the development of the bioeconomy; (4) finance for the energy transition; (5) finance for circular transition; (6) climate investments; (7) low-carbon investments; (8) investments in the development of alternative energy; (9) eco-friendly investments.